The Dynamics of Public Trust in Islamic Banking Products in Jambi City - Tarmuji; Wargo (CV. Zabags Qu Publish, 2025)
Public trust in Islamic banking products is a determining factor in the expansion and sustainability of the Islamic financial sector, particularly in regions with a predominantly Muslim population such as Jambi City. Although Islamic banks continue to grow institutionally, trust in their services is not uniform and is influenced by various factors including financial literacy, religious understanding, and the perceived alignment of products with Islamic values. This study aims to explore the dynamics of public trust in Islamic banking through a phenomenological approach that captures the lived experiences of individuals interacting with Islamic banks. Data were collected from selected informants including community members, Islamic bank employees, religious leaders, and micro-entrepreneurs using observation, interviews, and documentation. The results reveal that trust is formed gradually through knowledge dissemination, transparency in contracts, service quality, and the role of religious figures in validating the legitimacy of Sharia-compliant practices. These findings contribute theoretically by offering a context-based understanding of trust in Islamic finance, and practically by informing institutional strategies for enhancing public engagement and accountability in the delivery of Islamic banking products.